Novel Mutations Widen the Phenotypic Spectrum of Slow Skeletal/β-Cardiac Myosin (MYH7) Distal Myopathy - Phillipa J. Lamont; William Wallefeld; David Hilton‐Jones; Bjarne Udd; Zohar Argov; Alexandru Barboi; Carsten Bönneman; Kym M. Boycott; Kate Bushby; Anne M. Connolly; Nicholas P. Davies; Alan H. Beggs; et al. (2014)
Laing early onset distal myopathy and myosin storage myopathy are caused by mutations of slow skeletal/β-cardiac myosin heavy chain encoded by the gene MYH7, as is a common form of familial hypertrophic/dilated cardiomyopathy. The mechanisms by which different phenotypes are produced by mutations in MYH7, even in the same region of the gene, are not known. To explore the clinical spectrum and pathobiology, we screened the MYH7 gene in 88 patients from 21 previously unpublished families presenting with distal or generalized skeletal muscle weakness, with or without cardiac involvement. Twelve novel mutations have been identified in thirteen families. In one of these families, the father of the proband was found to be a mosaic for the MYH7 mutation. In eight cases, de novo mutation appeared to have occurred, which was proven in four. The presenting complaint was footdrop, sometimes leading to delayed walking or tripping, in members of 17 families (81%), with other presentations including cardiomyopathy in infancy, generalized floppiness, and scoliosis. Cardiac involvement as well as skeletal muscle weakness was identified in nine of 21 families. Spinal involvement such as scoliosis or rigidity was identified in 12 (57%). This report widens the clinical and pathological phenotypes, and the genetics of MYH7 mutations leading to skeletal muscle diseases.